Effect of magnetization on antibacterial, lipid-lowering and antioxidant activities of isoquinoline alkaloids - Xueting Feng; Weijie Li; Xiaoling Wang; Jie Tang; Shun Yao (Scientific Reports)
Abstract The magnetization strategy of isoquinoline alkaloids has been successfully used in the extraction and isolation, but the effect of the magnetization on biological activities of those alkaloids still deserves further investigation. Therefore, the antibacterial, lipid-lowering and antioxidant activities of five isoquinoline alkaloids (berberine, tetrahydroberberine, palmatine, tetrahydropalmatine and tetrahydropapavine) before and after magnetization were compared in this study, and the results showed that the relevant activities were enhanced after magnetization. Additionally, among the five magnetic derivatives studied, berberine magnetic derivative ([Ber·H]+[FeCl4]−) had the best antibacterial effect on S. aureus and E. coli with MIC of 200 and 800 µM, respectively; palmatine magnetic derivative ([Pal·H]+[FeCl4]−) showed the strongest lipid-lowering activity with IC50 of 429 mM, and the inhibitory effect and type on lipase was reversible and mixed inhibition of competition and non-competition type; tetrahydroberberine magnetic derivative ([THBer·H]+[FeCl4]−) had the strongest antioxidant activity. This study provides new ideas and references for the further application of magnetization strategy.